Long-term Impact of Mode of Delivery on Urinary Stress Incontinence - Neelam Saba, Imrana Rasheed, Shakeela Rasheed, Zarmin Ali Khan, Arooj Fatima, Sumbal Nadeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Among the female population, incontinence of urine varies 23-45%. Significant symptoms of urinary incontinence found in about 7%, of which 50% are urinary stress incontinence (USI). It is an unintentional urinary leakage from the urethra, during physical activity such as coughing, sneezing, laughing or exercise. Objective: To find the frequency of urinary stress incontinence (USI) and to find the long term impact of mode of delivery on urinary stress incontinence (USI). Methodology: Study Design: Cross sectional study Settings: Department of Obstetrics & Gynecology, Janki Devi Jamiat Singh Hospital Procedure for data Collection: 252 Patients with 48 to 58 years of age who answered questions related to urinary incontinence were included in the study. Data was entered and analyzed in SPSS. Age was presented as mean and ±SD. Mode of delivery, USI and Parity, etc… were presented as frequency and percentage. Chi square test was applied to compare the association between urinary stress incontinence with mode of delivery. p-value less than 0.05 was considered as significant. Results: Total 252 patients included, the mean age was 53.45+13.24 years. Most of the females 133(52.8%) had 52-57 years of age group. Number of Women who had vaginal deliveries were 165(65.5%) and those who had Cesarean section were 87(34.5%). The frequency of USI was reported as ‘never’ by 113(44.8%); ‘occasionally very less often’ by 63(25.0%); ‘sometimes with sneezing, coughing but not always’ by 47 (18.7%); and urine always leak with coughing and sneezing i-e severe USI by 29(11.5%). Severity increased with parity, and the frequency of USI was higher in women who had vaginal deliveries compared to cesarean deliveries. There was significant impact of mode of delivery on urinary stress incontinence. (P >0.05) Conclusion: The conclusion of the study is that the prevalence of USI was lowest among nulliparous women and higher in multiparous women. Frequency of urinary stress incontinence was higher in women who had multiple vaginal deliveries compared to cesarean deliveries. Other Significant risk factors for severe USI were age, multiparity and high body mass index (BMI >30).